Accessory Devices Frequently Used for Endoscopic Submucosal Dissection - Hyuk Soon Choi; Hoon Jai Chun (Korean Society of Gastrointestinal Endoscopy, 2017)
Endoscopic submucosal dissection (ESD) is increasingly being considered an essential component of treatment for early gastrointestinal cancers and subepithelial tumors. The ESD technique owes its popularity to the development of sophisticated instruments used for ESD. With an increase in the number of ESD procedures performed, there is rapid development in the number and types of endoscopic accessory devices used for such procedures. Despite the large numbers of new devices developed and marketed, the use of ESD instruments and accessory devices is largely determined by individual preferences and experiences. Accessory devices frequently used during ESD are important tools for ESD techniques. Each instrument possesses characteristic advantages and disadvantages associated with its use, and no one instrument is superior in all respects to others. In this article, we review the characteristics of endoscopic electrical knives, cap and hood, and hemostatic devices commonly used in ESD.